Cotton fabric decorated with manganese oxide nanorods as a supercapacitive flexible electrode for wearable electronics - Samuel, Edmund; Joshi, Bhavana; Kim, Yongil; Park, Chanwoo; Aldalbahi, Ali; El-Newehy, Mohamed; Lee, Hae-Seok; Yoon, Sam S. (Applied Surface Science, 2021)
We present the fabrication (using a hydrothermal process) and the properties of wearable fabrics decorated with ultrathin manganese oxide (MnO2) nanorods for supercapacitor applications. The superior mechanical durability of the supercapacitor was confirmed by cyclic voltammetry (CV) curves, which showed little change during 1000 bending cycles. The pseudocapacitive properties of the ultrathin MnO2 nanorods were confirmed by recording the CV curves at various scan rates. The galvanostatic charge-discharge curves at various specific currents confirmed the pseudocapacitance of MnO2. The ultrathin MnO2 nanorods exhibited a superior capacitance of 508 F.g(-1) and an energy density of 35.3 Wh.kg(-1). The MnO2 electrode with optimal properties demonstrated stable long-term cycling performance with 90% retention after 10,000 galvanostatic cycles.
Keywords: Cotton fabric; Manganese oxide; Ultrafine nanostructures; Wearable supercapacitors

Electrospun zinc-manganese bimetallic oxide carbon nanofibers as freestanding supercapacitor electrodes - Joshi, Bhavana; Samuel, Edmund; Kim, Yongil; Kim, Taegun; El-Newehy, Mohamed; Aldalbahi, Ali; Yoon, Sam S. (International Journal of Energy Research, 2022)
Flexible, lightweight, and freestanding zinc-manganese oxide carbon nanofibers are promising materials for the fabrication of portable electronic devices. Composite nanofibers were synthesized using terephthalic acid and sodium dodecyl sulfate. Terephthalic acid improves the flexibility of the composite fibers and facilitates the diffusion of electrolytic ions. Meanwhile, sodium dodecyl sulfate aids to elevate the metal (zinc) oxide particles to the surface of the nanofibers during annealing. The texturing of the carbon nanofiber surface with ZnO enhances the electrochemical activity of the composite fibers. Parametric studies were conducted by varying the weight ratio of zinc and manganese acetates from zero to unity. The optimal case with a ratio of 0.75 produces specific capacitances of 1080 and 817 F center dot g(-1) at current densities of 1 and 10 A center dot g(-1), respectively, with a wide potential window of 1.6 V, indicating outstanding energy storage capabilities. The capacitance retention was 92% after 10 000 galvanostatic charge-discharge cycles. The bending angle test confirmed the mechanical durability of the freestanding carbon nanofiber electrodes, and the corresponding change in the cyclic voltammetry curve was negligible.
Keywords: electrospinning; freestanding electrode; high-energy-density; supercapacitor; ZnMn2O4

Wearable fabric supercapacitors based on CNTs and polyhedral ZnO with a wide potential window - Samuel, Edmund; Joshi, Bhavana; Park, Chanwoo; Aldalbahi, Ali; El-Newehy, Mohamed; Lee, Hae-Seok; Yoon, Sam S. (International Journal of Energy Research, 2022)
Wearable electronic devices such as health monitors, sensors, and e-skin can be powered by lightweight, high-power supercapacitors. Using a binder-free and low-temperature hydrothermal method, polyhedral ZnO nanoparticles were grown on carbon nanotube (CNT)-decorated cotton fabric, which is friendly to human skin and highly wearable, inexpensive, and thus commercially viable. The concentration of the starting material, zinc acetate, was varied to optimize the electrochemical performance. The evenly spaced polyhedral ZnO facilitated efficient permeation of the electrolyte into the active material. The fabric filaments were decorated with CNTs to enhance electron transfer and the overall electrochemical processes. The symmetric cell comprised of cotton fabric decorated with ZnO polyhedron/CNT showed no discernible change in the cyclic voltammetry curves even after 500 bending cycles, demonstrating the mechanical durability of the electrode. The potential window of 1.6 V using a Na2SO4/K2SO4 aqueous dual-ion electrolyte improved the long-term electrochemical stability and increased the energy storage capacity. The capacitance retention was 94% after 5000 cycles at a current density of 1 A center dot g(-1), indicating long-term electrochemical stability. A specific capacitance of 375 F center dot g(-1) at a current density of 5 A center dot g(-1) and energy density of 33.3 Wh center dot kg(-1) at a power density of 2000 W center dot kg(-1) were recorded for the optimized electrode. Highlights Polyhedral ZnO was grown on cotton fabric using a hydrothermal process. The electrochemical performance was optimized by varying the zinc acetate concentration. The highest specific capacitance was 375 F center dot g(-1) at a current density of 5 A center dot g(-1). Under optimal conditions, the capacitance retention was 94% at N = 5000 cycles. The energy density of the electrode was as high as 33.3 Wh center dot kg(-1).
Keywords: carbon nanotube; Cotton fabric; hydrothermal process; wearable supercapacitor; ZnO polyhedron